HUBUNGAN PENDIDIKAN ORANG TUA DAN PENDAPATAN ORANG TUA TERHADAP PRESTASI BELAJAR GEOGRAFI DI SMA 2 SIJUNJUNG KABUPATEN SIJUNJUNG - Desmuliana, Dona - (STKIP PGRI Sumbar, 2014)
Education is any one it very importan for gived interest by goverment and society, reason is with education essense, disposition, and human personality formed. To recall goverment character in build effort and human formed. With high quality, the education problem be interest in Indonesia. The purpouse of research for found information, analyze and discuss about parents education connected and parents income towards geography student achievement in sma n 2 sijunjung, regency sijunjung. The kind of the research used descriptive cholera. The population geography student researth in sma n 2 sijunjung, regency sijunjung to number 99 peoples. The respondent sample used the total sampling to take in totality respondent sample to number 99 peoples. In cholera analyte to found conclusion as (1) the parents education have positive connected and signifikan influential towards geography study achievement in sma n 2 sijunjung, regency sijunjung (2) the parents income have positive connected and signifikan influence towards geography student achievement in sma n 2 sijunjung (3) the education and parents income in to coincide signifikan influential and positive towards geography student achievement in sma 2 sijunjung. Suggestion, the student is expected to sma 2 sijunjung districts to improve achievement, expected to parents of students in the high school sma 2 sijunjung to enhance chilrens learning facility and infrastructure equipment for the scool children and learn to student achievement obtained can be increased, the school is expected to sma 2 sijunjung more often provide counseling to students in the district sijunjung.